DEVELOP THE QUALITIES OF PROFESSIONAL CREATIVITY - Jalilov Nоdirjon Azamatovich (Galaxy International Interdisciplinary Research Journal, 2021)
The professional knowledge of the educator is characterized by creativity. Creativity is a way of professional life, a desire and skill to create a new pedagogical reality at the level of goals, content, technologies of the multifaceted educational process and system. Creativity helps the teacher to adapt to the flow of innovative changes. This article discusses the ideas and considerations for developing the qualities of professional creativity.